The Effect of Special Exercises Using a Proposed Electronic Device on Developing Some Skill and Motor Abilities among Young Boxing Players Aged 16–17 Years at Al-Rafidain Club - Shammakhi, Muhammad Haider (Indonesian Journal Publisher, 2025)
This study aims to design a proposed electronic skill–motor device and develop specialized exercises to enhance selected motor and skill abilities among young boxing players aged 16–17 years at Al-Rafidain Club. The experimental method was applied using a two-group design (experimental and control) with pre- and post-tests. The sample consisted of 12 boxers within the weight categories of 60 kg, 64 kg, and 69 kg, evenly divided between the two groups. The electronic device was designed with the assistance of a computer engineer and underwent two preliminary trials before being integrated into an eight-week specialized training program. The results revealed significant improvements in the reaction speed of straight and side punches, as well as dynamic balance, particularly in the experimental group compared to the control group. The findings confirm that utilizing the proposed electronic device provides more effective development of motor skills and punching performance than traditional training methods. The researcher recommends incorporating this device into regular training sessions and conducting further studies in other sports disciplines to evaluate its broader applicability.